2003
DOI: 10.1016/s1096-2867(03)00076-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal fecal assessment

Abstract: Fecal testing is a common component of most gastrointestinal work-ups. A multitude of diagnostic techniques are available for identifying parasites and pathogens, or showing abnormalities of flora. Optimal fecal assessment involves careful formulation of a differential list based on signalment, history, and clinical signs. Tests should be selected and interpreted based on their relative sensitivity and specificity for specific conditions. It is essential to use effective testing methods for the etiologies of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 11 publications
(20 reference statements)
1
47
0
Order By: Relevance
“…[Dunn and Keymer, 1986]). Additionally, sugar solutions, which have higher viscosity, have been suggested to require longer standing time compared to others [Broussard, 2003]. We further expected that higher quantities of parasite eggs and cysts would be recovered with sugar solution because its SG (1.27) was higher than that of zinc sulphate solution (1.18) or salt solution (1.18).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…[Dunn and Keymer, 1986]). Additionally, sugar solutions, which have higher viscosity, have been suggested to require longer standing time compared to others [Broussard, 2003]. We further expected that higher quantities of parasite eggs and cysts would be recovered with sugar solution because its SG (1.27) was higher than that of zinc sulphate solution (1.18) or salt solution (1.18).…”
Section: Discussionmentioning
confidence: 96%
“…Zinc sulphate solution is known for distorting most helminth eggs. However, sugar solution also tends to distort Giardia cysts, whereas zinc sulphate is considered ideal for their isolation [Broussard, 2003]. Particular attention should therefore be paid to these variations regarding the integrity of some parasite forms in order to avoid both false negatives and false positives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Broussard (2003), the Sheather technique is the one that has been most widely used in veterinary parasitology and the technique of Faust can already be considered to be the gold standard technique for Giardia spp. However, in the present study, the Faust and modified Sheather techniques showed low efficiency in making the diagnosis, given that these techniques also gave rise to morphological changes to the cysts, which often made it difficult to recognize them ( Figure 1D, E).…”
Section: Discussionmentioning
confidence: 99%